Race-performance parameters differentiating world-best from national-level swimmers: A race video analysis and machine-learning approach - Postiglione, G. L.; Abbott, S.; Newman, P.; Mitchell, L. G.; Elipot, M.; Barclay, G.; Cobley, S. (International Journal of Sports Physiology and Performance, 2025)
Background: Elite swimming performance is determined by a complex interplay of anthropometric, physiological, biomechanical, and technical factors. Previous research highlights how the 100-m freestyle demands explosive power, technical proficiency, and tactical acumen, yet factors that distinguish world-class swimmers from their closely performing (inter)national-level counterparts remain elusive. Purpose: To identify race-performance factors differentiating world-class swimmers in the 100-m freestyle.